An AN ANALYSIS FILM “EVERYTHING EVERYWHERE ALL AT ONCE” NIHILISM AND MULTIVERSAL METAPHORS (LITERATURE SEMIOTICS) - Toabnani, Aryanto (Universitas Samudra, 2023)
This research is a qualitative research because the data are in the form of words or sentences which are interpreted using literary semiotics to dissect the signs in the film so that the main marker is found. As well as to determine the signs associated with nihilism. This research is included in library research so that the signs are in the form of footage of scenes and dialogues in the material object only, namely the film Everything Everywhere All At Once.The research approach contained in the research used is to use a qualitative approach, which emphasizes an important thing from the nature of goods or services. From these goods or services in the form of events or phenomena of social phenomena that occur in these events which can be used as a valuable lesson for the development of theoretical concepts. Qualitative research is also research that uses a scientific background, namely with the intention of interpreting the phenomena that occur using various existing methods. This film never tries to show things to be wise, but instead questions the concepts above in a straightforward manner. in the end nothing matters which cannot be expressed in words, but how the author accepts all of this with an open mind. no need to many questions as no answers required. if life is the worst version then we are the best able to understand how the universe works.